Consequences and Predictors of Prolonged Tissue Expander Duration in Breast Reconstruction - Langdell, Hannah C.; Sergesketter, Amanda R.; Biswas, Sonali; Morris, Miranda; Zhang, Gloria X.; Atia, Andrew; Phillips, Brett T. (Journal of Reconstructive Microsurgery, 2023)
Background Tissue expanders (TEs) are temporary devices used in breast reconstruction, which are generally removed within 1 year. There is a paucity of data regarding the potential consequences when TEs have longer indwelling times. Thus, we aim to determine whether prolonged TE implantation length is associated with TE-related complications.Methods This is a single-center retrospective review of patients who underwent TE placement for breast reconstruction from 2015 to 2021. Complications were compared between patients who had a TE for >1 year and <1 year. Univariate and multivariate regressions were used to evaluate predictors of TE complications.Results A total of 582 patients underwent TE placement and 12.2% had the expander for >1 year. Adjuvant chemoradiation, body mass index (BMI), overall stage, and diabetes predicted the duration of TE placement (p ≤ 0.006). Rate of return to the operating room was higher in patients who had TEs in place >1 year (22.5 vs 6.1%, p < 0.001). On multivariate regression, prolonged TE duration predicted an infection requiring antibiotics, readmission, and reoperation (p < 0.001). Reasons for longer indwelling times included need for additional chemoradiation (79.4%), TE infections (12.7%), and requesting a break from surgery (6.3%).Conclusion Indwelling TEs for >1 year are associated with higher rates of infection, readmission, and reoperation even when controlling for adjuvant chemoradiation. Patients with diabetes, a higher BMI, advanced cancer stage, and those requiring adjuvant chemoradiation should be advised they may require a TE for a longer time interval prior to final reconstruction.
Keywords: tissue expander; breast reconstruction; reoperation; infection